A general strategy for the structural determination of carbohydrates by multi-dimensional NMR spectroscopies. (1st September 2021) - Shi, Qi; Yan, Jingyu; Jiang, Bin; Chi, Xiujuan; Wang, Jihui; Liang, Xinmiao; Ai, Xuanjun
Abstract: Two-dimensional NMR spectroscopies are one of the most frequently used techniques for the structural determination of carbohydrates. However, the data analysis is challenging because of the signal overlap in the 1 H homonuclear correlation spectra. We attempted to explore a general strategy for the structural determination of carbohydrates by combined multi-dimensional spectroscopies. The strategy was applied to a human milk oligosaccharide lacto-N-difucohexaose I, that has been previously studied by conventional two-dimensional NMR spectroscopy. Assignment of the intra-residue resonances of the hexasaccharide using the three-dimensional spectrum was straightforward. Consequently, data analysis of the multi-dimensional spectra was significantly simplified, leading to a quicker determination of the intra- and inter-residue connections in the hexasaccharide. Application of the NMR strategy to chondroitin sulfate from bovine cartilage revealed two repeating disaccharide regions of the A and C units of chondroitin sulfate, indicating the high potential of this technique for the structural determination of complex polysaccharides. Highlights: A general strategy was proposed for structural determination of carbohydrate. The NMR strategy does not have the 2D signal-overlap problem. Untreated polysaccharide could be used for NMR structural determination. Two repeating disaccharide regions in chondroitin sulfate were verified.